ON THE SOLUTION OF THE EQUATION 5k=1x+1y+1z ON THE SET OF NATURAL NUMBERS N{60n+1, n N} - Aslanyan, E.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the present paper it is shown that for every number k ot160, the equation 5k=1x+1y+1z has at least one solution (x, y, z)N.